Ethnic Networks and the Employment of Asylum Seekers: Evidence from Germany - Felix Stips; Krisztina Kis-Katos (Institute of Labor Economics (IZA), 2020)
Using novel registry data on the population of asylum seekers in Germany for the period from 2010 to 2016, and quasi-experimental variation induced by German allocation policies, we identify causal effects of the size and composition of local co-national networks on formal labor market access of asylum seekers. While the individual employment probability is not linked to network size, it increases with the number of employed local co-national asylum seekers and decreases with the number of non-employed network members, thereby underlining the central importance of network quality.
Keywords: F22; J61; R23; 330; social networks; refugees; employment; Germany; dispersal policies